2020
DOI: 10.1007/s00277-020-04173-5
|View full text |Cite
|
Sign up to set email alerts
|

Disease management of patients with immune thrombocytopenia—results of a representative retrospective survey in Germany

Abstract: Clinical research has resulted in an improvement of treatment options for patients with immune thrombocytopenia (ITP) over the last years. However, only few data exist on the real-life management of patients with ITP. To expand the knowledge, a multicenter, national survey was undertaken in 26 hematology practices distributed all over Germany. All patients with a diagnosis of ITP were documented using questionnaires, irrespective of the diagnosis date over a period of 2 years. Overall, data of 1023 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…In the periods before, during and after TPO-RA treatment, oral corticosteroids were prescribed in 64.4% (18-month period), 43.4% (median of approximately 9 months) and 36.1% (median of approximately 14 months) of all patients, respectively. In support of our data, a retrospective analysis of data (gathered via questionnaires) from 26 German hematology centers reported that corticosteroids were the most commonly prescribed first-line treatment for ITP received by 45% of patients (41% underwent a watch and wait approach); 36% and 28% of patients received corticosteroids in the second and third line, respectively [21]. Thus, our study builds upon published data, using a robust and generalizable statutory healthcare prescription database covering approximately 90% of the German population.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the periods before, during and after TPO-RA treatment, oral corticosteroids were prescribed in 64.4% (18-month period), 43.4% (median of approximately 9 months) and 36.1% (median of approximately 14 months) of all patients, respectively. In support of our data, a retrospective analysis of data (gathered via questionnaires) from 26 German hematology centers reported that corticosteroids were the most commonly prescribed first-line treatment for ITP received by 45% of patients (41% underwent a watch and wait approach); 36% and 28% of patients received corticosteroids in the second and third line, respectively [21]. Thus, our study builds upon published data, using a robust and generalizable statutory healthcare prescription database covering approximately 90% of the German population.…”
Section: Discussionsupporting
confidence: 79%
“…While the preferred sequencing of ITP treatment is well defined on an international and German level, a translational delay from empirical guidelines to realworld clinical practice is well recognized. Indeed, contrary to guidelines, persistent overuse of corticosteroids has been observed [19][20][21]. The present study evaluated treatment patterns prior to, during and after the use of TPO-RAs in adult patients with ITP in the German healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, in a German survey of 1023 patients, 62% of patients receiving steroids as first-line treatment therapy received them for up to 6 months, and 29% received them for more than a year during second-and even third-line treatment. 11 In many patients, ITP becomes persistent or chronic, and second-line treatment may thus be warranted. 5,12,13 In this regard, it should be considered that limiting corticosteroids to the first line of therapy allows earlier transition to secondline therapy.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, in a German survey of 1023 patients, 62% of patients receiving steroids as first-line treatment therapy received them for up to 6 months, and 29% received them for more than a year during second- and even third-line treatment. 11…”
Section: Introductionmentioning
confidence: 99%
“…Our study sample was representative of the general German ITP population, as shown by comparison to patients in a national survey (2016–2017) [ 25 ]. In both study cohorts, over 50% of patients had chronic ITP (>12 months); corticosteroids and IVIg were the most frequently used treatments prior to romiplostim initiation.…”
Section: Discussion/conclusionmentioning
confidence: 99%